SLiMS Implementation in SMAN 1 Sei Suka Library to Improve Education Quality - Muhammad Rasyid Ridlo; Dirmansyah; Rayyana Dario Silva; Johanes Ranto Prancis; T. Kasa Rullah Adha; Dedy Arisandi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
SMA Negeri 1 Sei Suka is one of the senior high schools located in Sei Suka District, Batu Bara Regency, North Sumatra Province. This school has various facilities including a library to support student learning activities. However, the library is still managed manually and has not been automated. The development of library information systems in partner libraries aims to improve library quality, especially in web-based library information systems through SLiMS. The method used as a solution to partner problems is initial observation, training for librarians, assistance to librarians and socialization of SLiMS utilization. The results of the service implementation show that SLiMS as a library information system in service partners has great benefits for librarians and libraries, especially in simplifying library operations. There was deep enthusiasm from librarians, teachers and students towards the utilization of SLiMS for partner libraries. Based on the results of the service implementation, it is concluded that a web-based library information system using SLiMS is more effective to use than a manual system